1979
DOI: 10.1007/bf02020517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fats and triiodothyronine administration on the lipid components of serum and tissues in the rat

Abstract: Twelve groups of rats were included in this study. Six groups (3 males and 3 females) received high fat diets containing 20% of either peanut oil, maize oil or lard. The other six groups received the same diets plus triiodothyronine. Triiodothyronine T3 added to diets containing peanut oil caused slight increase in total serum lipids in female rats, while in male rats serum total lipids were increased about 20-fold. T3 administration caused almost no change in aortic total and all lipid fractions in male rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Interestingly enough, according to recent reports, T 3 added to diets containing peanut oil increased serum lipids in rats, sometimes even up to 20-fold [35], whereas T 3 was found to increase cholesterol biosynthesis in the liver through the activation of de novo protein synthesis [36, 37]. Furthermore, T 3 , insulin, and their combination markedly stimulate cholesterol synthesis in cultured human skin fibroblasts [38], and in recent studies FT 3 has been even shown to exert a beta-cell protective effect [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, according to recent reports, T 3 added to diets containing peanut oil increased serum lipids in rats, sometimes even up to 20-fold [35], whereas T 3 was found to increase cholesterol biosynthesis in the liver through the activation of de novo protein synthesis [36, 37]. Furthermore, T 3 , insulin, and their combination markedly stimulate cholesterol synthesis in cultured human skin fibroblasts [38], and in recent studies FT 3 has been even shown to exert a beta-cell protective effect [39, 40].…”
Section: Discussionmentioning
confidence: 99%